2023
DOI: 10.1186/s12967-022-03856-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of genetic aberrations and tumor immune microenvironment in primary acral melanoma

Abstract: Background Acral melanoma (AM) is the most common subtype in Chinese melanoma patients with a very poor prognosis. However, our understanding of the disease pathogenesis and molecular landscape is limited by the few studies that have been conducted. Here, we profiled the clinical characteristics, mutational landscapes and tumor immune microenvironment of AM patients to gain insights into disease characteristics and potential treatment strategies. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Due to the rarity of these mutations in cutaneous melanomas, their clinical implications are still unclear [ 66 ]. For example, ARID2 mutations seem more frequent in acral melanomas, but their significance remains unknown [ 82 ]. An in vitro study demonstrated that ARID2 acts as an immunomodulator in melanomas, and ARIDS2 knock-out enhances the effect of immune checkpoint inhibitors in melanoma cell lines [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the rarity of these mutations in cutaneous melanomas, their clinical implications are still unclear [ 66 ]. For example, ARID2 mutations seem more frequent in acral melanomas, but their significance remains unknown [ 82 ]. An in vitro study demonstrated that ARID2 acts as an immunomodulator in melanomas, and ARIDS2 knock-out enhances the effect of immune checkpoint inhibitors in melanoma cell lines [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study demonstrated that ARID2 acts as an immunomodulator in melanomas, and ARIDS2 knock-out enhances the effect of immune checkpoint inhibitors in melanoma cell lines [ 83 ]. FGFR2 mutations have been described in various melanoma subtypes, including ALM or desmoplastic melanomas [ 82 , 84 , 85 ]. These findings are exciting as FGFR2 mutated melanomas can benefit from targeted therapy [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, CNV in AM were common in CCND1 (19.3%), CDK4 (cyclin-dependent kinase 4) (19.3%), MDM2 (mouse double minute 2 homolog) (14.5%), and FGF19 (fibroblast growth factor 19) (12%). Moreover, CDK4 amplifications were independently linked to shorter OS ( 32 ). Similarly, frequent alterations in the CDK4 signaling pathway, which facilitates the G1 to S-cell cycle transition and tumor progression, were found in a study of 514 cases of AM.…”
Section: Mutational Landscapementioning
confidence: 99%
“… 14 16 AM exhibits significant intra‐tumoral and inter‐tumoral heterogeneity, as well as a highly immune‐suppressive TME and a complex intercellular communication network. 17 , 18 Despite the recognized importance of CD8+ T cells in tumors, our current understanding of them remains limited, particularly in melanoma, where there is a lack of gene markers that accurately describe the characteristics and functions of CD8+ T cells. Furthermore, there is currently no effective gene signature related to CD8+ T cells to predict the prognosis of melanoma patients or guide their treatment decisions.…”
Section: Introductionmentioning
confidence: 99%